Inclusive Islamic and Nature-Based Primary School Model - Muhyani, Muhyani; Shidqy, Mukhrij (ATTA`DIB, 2025)
This study aims to formulate a model of an inclusive Islamic and nature-based elementary school. Many children with special needs have not received formal basic education due to the limited number of Special Schools (SLB) in Indonesia. The capacity of SLB and inclusive schools is only 3%, leaving 97% of children with special needs without access to formal education. A qualitative research method was employed, involving observation and in-depth interviews. The results show that an inclusive Islamic and nature-based elementary school is a public school that accepts children with special needs, accompanied by special assistant teachers. Activities include spiritual aspects (reading the Quran, congregational prayers, memorizing hadiths) and cognitive aspects (learning in the classroom and utilizing nature). Children with special needs can participate in activities without being required to master academic aspects, but develop life skills. The findings suggest that the government’s limitations can be overcome by public schools accepting children with special needs, enabling them to actualize themselves. As Muslims, it is obligatory to teach all children to worship without discrimination. It is hoped that educational institutions will participate in the jihad of teaching Islam to all people, including those with special needs.